2021
DOI: 10.1002/mdc3.13261
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Response to Long‐Term Treatment with Intravenous Immunoglobulin in Patients with Stiff Person Syndrome

Abstract: BackgroundStiff Person Syndrome (SPS) is an autoimmune condition involving antibodies against several components of the inhibitory synapse in the spinal cord, with Glutamic Acid Decarboxylase (GAD) antibodies being the predominant immune marker. SPS affects approximately 1 patient per million population per year. The effect of IVIG has been established but studies on long term efficacy of regular IVIG are limited. ObjectivesReview clinical details and long-term treatment response using a patient-reported quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Along with anti‐GAD antibodies, antibodies against glycine receptors were existent in 14 patients 22,28,30,32 . Among 59 patients who were anti GAD antibodies‐negative, 17 had antiglycine receptor antibodies 20,28,30 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Along with anti‐GAD antibodies, antibodies against glycine receptors were existent in 14 patients 22,28,30,32 . Among 59 patients who were anti GAD antibodies‐negative, 17 had antiglycine receptor antibodies 20,28,30 …”
Section: Resultsmentioning
confidence: 99%
“…This scoring system was used for 38 out of 95 SPS patients 22,25,28,31,32 . Bose et al used the Birmingham Response to Immunomodulatory Therapy (BRIT) scoring system consisting of a functional ability score which was assessed by mRS and a quality of life (QoL) score, and mentioned significant improvement in 19 SPS patients receiving IVIG 20 . A randomized, double‐blinded, placebo‐controlled, crossover trial of monthly IVIG showed a notable reduction in stiffness, as assessed by the use of scores of the distribution‐of‐stiffness index and the heightened sensitivity scale from baseline (first month) to the second and third month of each treatment phase, which stabilized during washout and increased again on switching to placebo 23 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SPS is notoriously difficult to diagnose as it is rare, uncommonly considered, and symptoms evolve over time. A retrospective cohort of 23 patients with SPS spectrum disorders reported that patients were diagnosed on average 3.5 years after initial symptoms and first began immunomodulatory treatment with IVIG more than 5 years after symptom onset [ 5 ]. The initial presenting symptoms, as assessed by Tsiortou et al and colleagues in a retrospective cohort of 57 patients, were slowly progressive proximal leg stiffness which then progressed to muscle spasms, stiffness in the thoracolumbar spine, muscle rigidity, and hyperreflexia [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…When IVIG was stopped, the patients experienced a rebound worsening of their stiffness [ 7 ]. Reports of long-term follow-up of patients on IVIG therapy show that the patients remained stable and continued to improve clinically even after 3–5 years of therapy [ 5 ].…”
Section: Discussionmentioning
confidence: 99%